Saving forest ecosystems - Russell, George H.; Nolan, Mary Lee; Soare, Thomas F.
The learning objectives of this programme are : 1) Information concerning the condition of the forests of the world and the threats that face them will be provided. 2) The ways in which forest ecosystems are essential to long-term planetary life will be discussed. 3) The process of clear-cutting, and the dangers that this practice creates, economically and ecologically, will be explained.